RANCANG BANGUN SISTEM INFORMASI PENJUALAN ONLINE PADA TOKO PONDOK BUSANA - Nasril Nasril; Indri Putri Effendy (JURNAL LENTERA ICT, 2024)
The E-Filing System at the LP3I Polytechnic is a web-based document storage system designed to manage archives and documents electronically. This system can store various types and formats of digital documents, facilitating the process of storing, searching, grouping, and managing documents in a structured manner. The implementation of the E-Filing system aims to increase efficiency and effectiveness in administrative document management, while reducing reliance on paper, which can generate waste and high operational costs. Furthermore, this system is designed to minimize the risk of document loss, damage, or duplication, which often occurs in manual filing systems. With the E-Filing system, document management can be carried out centrally, securely, and easily accessed by authorized parties anytime and anywhere via the internet. Implementation of this system is expected to improve the performance of administrative staff in managing documents more quickly, accurately, and organized, while also supporting the creation of a more modern, efficient, and environmentally friendly work environment.